Pengembangan Buku Panduan Konseling Kelompok Dengan Teknik Self Management Untuk Meminimalisasi Prokrastinasi Akademik Siswa - Komang Novi Widi Antariyani; Ni Ketut Suarni; Gede Nugraha Sudarsana (Universitas Pendidikan Ganesha, 2022)
The product developed in this research is a group counseling guide book with self-management techniques to minimize the vocational high students’ academic procrastination. By using 4D development model proposed by Thiagarajan, (1974), the acceptance assessment of this guidebook was assessed by 5 experts in the field of counseling guidance. The results of data analysis in the implementation of the product content validity test with indicators of usability, feasibility, and accuracy obtained the results of CVR = 22 and CVI = 1 (very appropriate). This result indicated the eligibility criteria performed by the group counseling manual. To test the guidebook’s effectiveness, the study involves 10 students to be participated in one group pre-test and post-test design method. From this test, it was obtained tcount = 6.61 and ttable = 2.307 which means the value of tcount > ttable, these results indicate that the development of group counseling guidebooks with self-management techniques is effective to minimize academic procrastination of vocational high students